Precision of plasma urea and electrolytes estimated by the AutoAnalyzer - Campbell, D. G. (1966)
The precision of sodium, potassium, chloride, and bicarbonate analyses carried out by the AutoAnalyzer has been studied under routine laboratory conditions. From the results it is concluded that a further increase in precision is desirable.